(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2024)
This paper describes an experimental study and comparison of the frequency responses of an electropneumatic positioning system with a rod and a rodless pneumatic cylinder. An experimental rig is set up to study the Bode magnitude and phase plots of an electropneumatic positioning system with different types of pneumatic cylinders, and the critical frequencies of the system are determined. A virtual instrument is used to collect experimental data. The processing and process control are automatically performed by a PC and the corresponding NI interface board. The frequency response of the system is defined by two graphs - Amplitude-frequency response (AFR) and Phase-frequency response (PFR). From the presented characteristics, the critical frequencies are determined for both systems - with double out rod and rodless cylinder. As a result of the research, it was established that in a pneumatic positioning system with a double-sided out rod cylinder, the critical frequency is higher than the system with rodless cylinder. This indicates the better dynamic properties of the system. The advantages of the rodless pneumatic cylinder are that its design occupies less embedding space compared to a cylinder with a double out rod, which requires twice the clearances for equal working strokes in industrial electropneumatic positioning systems.